2020
DOI: 10.1177/0300060520903658
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and outcome of intelligently inflatable reduction in conjunction with percutaneous pedicle screw fixation for treating thoracolumbar burst fractures

Abstract: Objective This study was performed to describe a new minimally invasive surgical technique and to explore its effects and practical use in the clinical setting. Methods In total, 22 patients with single-segment thoracolumbar burst fractures underwent treatment with an intelligently inflatable reduction device before common percutaneous pedicle screw fixation. Complications were recorded and short-term effectiveness was evaluated using the visual analogue scale (VAS) sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The other studies were prospective or retrospective cohort studies. The posterior (PO (n = 75)17-77, PP (n = 39) ( Fan et al, 2017 ; Kocis et al, 2020 ; Lee et al, 2013 ; Lyu et al, 2016 ; Pishnamaz et al, 2015 ; Vanek et al, 2014 ; Wang et al, 2017 ; Wang et al, 2013 ; Zhang et al, 2016 ; Zou et al, 2017 ; Afzal et al, 2008 ; Altay et al, 2007 ; Andress et al, 2002 ; Butt et al, 2007 ; Caruso et al, 2019 ; Caruso et al, 2018 ; Ding et al, 2021 ; He et al, 2013 ; Jiang et al, 2020 ; Kerschbaumer et al, 2019 ; Korovessis et al, 2008b ; Korovessis et al, 2017 ; Korovessis et al, 2014 ; Li et al, 2016b ; Manson et al, 2020 ; Padalkar and Mehta, 2017 ; Podet et al, 2020 ; Proietti et al, 2014 ; Sanli et al, 2019 ; Shao et al, 2020 ; Shin et al, 2020 ; Teyssedou et al, 2012 ; Trungu et al, 2019 ), SA (n = 13)) ( He et al, 2013 ; Kerschbaumer et al, 2019 ; Teyssedou et al, 2012 ; Costa et al, 2009 ; Grelat et al, 2018 ; Hartmann et al, 2012 ; Hartmann et al, 2015 ; Klezl et al, 2011 ; Maestretti et al, 2014 ; Saget et al, 2014 ; Schmelzer-Schmied et al, 2009 ; Schulz et al, 2015 ), and anterior (AO (n = 5)) ( Wood et al, 2005 ; Shin et al, 2020 ; Liang et al, 2017 ; Oskouian et al, 2006 ; Smith et al, 2010 ; Yang et al, 2012 ) approaches seemed to be the most often reported surgical techniques. As an anterior scopic technique only thoracoscopy was reported, in the found studies it was not used as the sole surgical technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other studies were prospective or retrospective cohort studies. The posterior (PO (n = 75)17-77, PP (n = 39) ( Fan et al, 2017 ; Kocis et al, 2020 ; Lee et al, 2013 ; Lyu et al, 2016 ; Pishnamaz et al, 2015 ; Vanek et al, 2014 ; Wang et al, 2017 ; Wang et al, 2013 ; Zhang et al, 2016 ; Zou et al, 2017 ; Afzal et al, 2008 ; Altay et al, 2007 ; Andress et al, 2002 ; Butt et al, 2007 ; Caruso et al, 2019 ; Caruso et al, 2018 ; Ding et al, 2021 ; He et al, 2013 ; Jiang et al, 2020 ; Kerschbaumer et al, 2019 ; Korovessis et al, 2008b ; Korovessis et al, 2017 ; Korovessis et al, 2014 ; Li et al, 2016b ; Manson et al, 2020 ; Padalkar and Mehta, 2017 ; Podet et al, 2020 ; Proietti et al, 2014 ; Sanli et al, 2019 ; Shao et al, 2020 ; Shin et al, 2020 ; Teyssedou et al, 2012 ; Trungu et al, 2019 ), SA (n = 13)) ( He et al, 2013 ; Kerschbaumer et al, 2019 ; Teyssedou et al, 2012 ; Costa et al, 2009 ; Grelat et al, 2018 ; Hartmann et al, 2012 ; Hartmann et al, 2015 ; Klezl et al, 2011 ; Maestretti et al, 2014 ; Saget et al, 2014 ; Schmelzer-Schmied et al, 2009 ; Schulz et al, 2015 ), and anterior (AO (n = 5)) ( Wood et al, 2005 ; Shin et al, 2020 ; Liang et al, 2017 ; Oskouian et al, 2006 ; Smith et al, 2010 ; Yang et al, 2012 ) approaches seemed to be the most often reported surgical techniques. As an anterior scopic technique only thoracoscopy was reported, in the found studies it was not used as the sole surgical technique.…”
Section: Resultsmentioning
confidence: 99%
“…However, PP requires a longer learning curve and may expose the surgeon to more radiation ( Court and Vincent, 2012 ). Moreover, it is rarely used in combination with neural decompression ( Wood et al, 2005 ; Fan et al, 2017 ; Kocis et al, 2020 ; Lee et al, 2013 ; Lyu et al, 2016 ; Pishnamaz et al, 2015 ; Vanek et al, 2014 ; Wang et al, 2017 ; Wang et al, 2013 ; Zhang et al, 2016 ; Zou et al, 2017 ; Afzal et al, 2008 ; Altay et al, 2007 ; Andress et al, 2002 ; Butt et al, 2007 ; Caruso et al, 2019 ; Caruso et al, 2018 ; Ding et al, 2021 ; He et al, 2013 ; Jiang et al, 2020 ; Kerschbaumer et al, 2019 ; Korovessis et al, 2008b ; Korovessis et al, 2017 ; Korovessis et al, 2014 ; Li et al, 2016b ; Manson et al, 2020 ; Padalkar and Mehta, 2017 ; Podet et al, 2020 ; Proietti et al, 2014 ; Sanli et al, 2019 ; Shao et al, 2020 ; Shin et al, 2020 ; Teyssedou et al, 2012 ; Trungu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although bone density-related data were not collected in this study, the abnormal increase in Cobb angles postoperatively in elderly female patients strongly suggests that osteoporosis is one of the risk factors for long-term complications following burst fractures [26][27][28][29]. Previous studies have indicated that PKP is ineffective for height restoration and improvement in segmental kyphosis, therefore cement augmentation or intelligently in atable reduction combined with SFTV or STV treatment is the rst choice for elderly patients with osteoporotic thoracolumbar burst fractures [30,31]. This information can also guide the surgical selection for patients at high risk of postoperative complications following thoracolumbar burst fractures.…”
Section: Discussionmentioning
confidence: 99%
“…5 With the development of orthopedic internal fixation instruments and medical imaging, as well as the improvement of surgical strategy, percutaneous minimally invasive pedicle screw internal fixation has achieved significant curative effect in the treatment of thoracolumbar spine fractures, which can significantly reduce the pain of patients, shorten the hospitalization time, reduce intraoperative bleeding, and improve the quality of life of patients. 6 This study was carried out with its main purpose of investigating the effect of minimally invasive percutaneous pedicle screw fixation in the treatment of thoracolumbar vertebral fractures and its impact on the quality of life. The specific details are reported as follows.…”
Section: Introductionmentioning
confidence: 99%
“… 5 With the development of orthopedic internal fixation instruments and medical imaging, as well as the improvement of surgical strategy, percutaneous minimally invasive pedicle screw internal fixation has achieved significant curative effect in the treatment of thoracolumbar spine fractures, which can significantly reduce the pain of patients, shorten the hospitalization time, reduce intraoperative bleeding, and improve the quality of life of patients. 6 …”
Section: Introductionmentioning
confidence: 99%